Model Hubungan Citra Merek dan Minat Beli Ulang : Peran Kepuasan Pelanggan dan Kesetiaan Pelanggan - Achmad Chairudin; Santi Retno Sari (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2021)
Purpose The aim of this research is to get a better understanding to answer customer perceptions of the relationship between brand image and repurchase intention through sequential mediation from consumer satisfaction to customer loyalty. Methodology A total of 101 employees with purposive sampling technique as the sample in this study. Hypothesis testing technique using multiple linear regression and mediation using macro process model No. 6 Findings The model of the relationship between brand image and repurchase intention through two mediation of customer satisfaction and customer loyalty is confirmed. Suggestions for further research to increase the number and coverage of the population. The practical implication is that companies must always improve and maintain their brand image to increase repurchase interest, because this increases customer satisfaction and loyalty.